2009
DOI: 10.1094/mpmi-22-11-1455
|View full text |Cite
|
Sign up to set email alerts
|

Hexanoic Acid-Induced Resistance Against Botrytis cinerea in Tomato Plants

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
139
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(152 citation statements)
references
References 54 publications
(72 reference statements)
11
139
1
Order By: Relevance
“…therein). For example, hexanoic acid, a molecule with a similar structure to GLVs, has been shown to act as a priming agent in tomato (Solanum lycopersicum) plants against an infection by the necrotrophic fungus Botrytis cinerea, leading to a reduced accumulation of reactive oxygen species in primed plants (Vicedo et al, 2009;Kravchuk et al, 2011;Finiti et al, 2014). Since the GLVs E-2-hexenal (E-2-HAL), Z-3-HOL, E-2-hexenol, and Z-3-HAC also have been reported to be emitted by perennial ryegrass (Lolium perenne) after infection with Fusarium poae (Panka et al, 2013) and by wheat (Triticum aestivum) seedlings after infection with Fusarium graminearum (Piesik et al, 2011), one may speculate that GLVs not only serve as a priming agent against the impending threat of herbivorous insects but rather constitute a general warning and priming mechanism against insects, bacteria, and fungi alike.…”
mentioning
confidence: 99%
“…therein). For example, hexanoic acid, a molecule with a similar structure to GLVs, has been shown to act as a priming agent in tomato (Solanum lycopersicum) plants against an infection by the necrotrophic fungus Botrytis cinerea, leading to a reduced accumulation of reactive oxygen species in primed plants (Vicedo et al, 2009;Kravchuk et al, 2011;Finiti et al, 2014). Since the GLVs E-2-hexenal (E-2-HAL), Z-3-HOL, E-2-hexenol, and Z-3-HAC also have been reported to be emitted by perennial ryegrass (Lolium perenne) after infection with Fusarium poae (Panka et al, 2013) and by wheat (Triticum aestivum) seedlings after infection with Fusarium graminearum (Piesik et al, 2011), one may speculate that GLVs not only serve as a priming agent against the impending threat of herbivorous insects but rather constitute a general warning and priming mechanism against insects, bacteria, and fungi alike.…”
mentioning
confidence: 99%
“…The molecular basis of priming has recently started to be unraveled, but is still poorly understood. In recent years, our research group has focused on studying inducers of resistance, such as natural 6C monocarboxylic hexanoic acid (Hx), which displays effectiveness in tomato plants against necrotrophic fungi B. cinerea (Leyva et al, 2008;Vicedo et al, 2009). Treating the roots of 4-week-old plants with Hx at concentrations below 1 mM for 48 h prior to infection has been reported to significantly reduce disease incidence (Vicedo et al, 2009).…”
Section: Priming Stage Induced By Natural or Quemical Compoundsmentioning
confidence: 99%
“…In Fortune Mandarin, Llorens et al (2013) have demonstrated that JA-signaling and callose priming are required for Hx-IR. Moreover, Hx treatment has been reported to protect tomato plants against hemi-biotrophic bacterium P.syringae pv tomato DC3000 (Vicedo et al, 2009). Recently, some studies have revealed that in this pathosystem, Hx treatment seems to counteract the negative effect of pathogen coronatine (COR), which requires JA-Ile on the SA pathway (Scalschi et al, 2013 (Britto and Kronzucker, 2002).…”
Section: Priming Stage Induced By Natural or Quemical Compoundsmentioning
confidence: 99%
See 2 more Smart Citations